Investigation of the Correlation between Postherpetic Itch and Neuropathic Pain over Time - Rie Ishikawa; Masako Iseki; Rie Koga; Eiichi Inada (Pain Research and Management)
Postherpetic itch (PHI), or herpes zoster itch, is an intractable and poorly understood disease. We targeted 94 herpes zoster patients to investigate their pain and itch intensities at three separate stages of the condition (acute, subacute, and chronic). We used painDETECT questionnaire (PDQ) scores to investigate the correlation between PHI and neuropathic pain. Seventy-six patients were able to complete follow-up surveys. The prevalence of PHI was 47/76 (62%), 28/76 (37%), and 34/76 (45%) at the acute, subacute, and chronic stages, respectively. PHI manifestation times and patterns varied. We investigated the relationship of PHI with neuropathic pain using the visual analog scale (VAS), which is a measure of pain intensity, and the PDQ, which is a questionnaire used to evaluate the elements of neuropathic pain. The VAS and PDQ scores did not differ significantly between PHI-positive and PHI-negative patients. A large neuropathic component was not found for herpes zoster itch, suggesting that neuropathic pain treatments may not able to adequately control the itch. Accordingly, we suggest that a more PHI-focused therapy is required to address this condition.